Numerical analysis of water based CNTs flow of micropolar fluid through rotating frame. (April 2020) - Nadeem, S.; Abbas, Nadeem; Elmasry, Yasser; Malik, M.Y.
Highlights: Flow of micropolar fluid in rotating frame is considered. Both SWCNT and MWCNT carbon nanotubes are considered. Numerically solutions are developed through shooting method via MAPLE software. Abstract: Background: In this article, the nanomaterial flow of micropolar fluid in rotating frame is considered. The SWCNT and MWCNT with base fluid namely pure water is also taken into account to analyze the flow behavior over stretching surface. Mathematical model have been constructed under the nanomaterial of micropolar fluid. Method: The governing equations have been developed in the form of system of partial differential equations. The partial differential equations are transformed into ordinary differential equations using similarity transformations. The transformed system has been solved through MAPLE software. Results: The physical parameters like as thermal slip effects, velocity slip effects and magnetic hydrodynamics on the micropolar nanofluid are presented by tables and graphs. Surprisingly in the rotating parameter, F′′(0) and − θ′(0) increases for higher values of the rotating parameter while opposite to be noted for G′′(0). The Nusselt number and skin friction increases for higher values of micropolar parameter but MWCNT achieves higher heat transfer as associated to SWCNT.